Asymmetric Intermolecular Conjugate Addition of 3-Substituted 2-Benzofuranones to Maleimides via Noncovalent NHC Catalysis - Mondal, Bhaskar Deb; Gorai, Sadhan; Guin, Joyram (Synlett, 2024)
An efficient N-heterocyclic carbene (NHC)-catalyzed asymmetric conjugate addition reaction to afford synthetically challenging benzofuranone derivatives having vicinal all-carbon quaternary and tertiary stereocenters is presented. The reaction operates solely through noncovalent interaction between a newly designed NHC and the substrates, providing access to a series of functionalized benzofuranones in good yields and with high ee values. The protocol applies to preparative-scale synthesis. A catalytic cycle involving a noncovalent substrate–NHC interaction is implicated in the process, based on a mechanistic control study.
Keywords: asymmetric catalysis; N-heterocyclic carbenes; noncovalent interaction; conjugate addition; benzofuranones; maleimides